Biological therapies for asthma - Couillard Castonguay, S; Pavord, I (Elsevier, 2021)
Five to 10% of asthma patients remain symptomatic and/or have asthma attacks despite adequate inhaled and systemic therapy. Eosinophilic, type 2 airway inflammation is seen in half of these patients with severe asthma. There is now convincing evidence that type 2 inflammation drives susceptibility to asthma attacks and is associated with a good response to biological therapies. Monoclonal antibodies targeting immunoglobulin E, interleukin (IL)-5 and IL-4/13 now have established efficacy in severe type 2 asthma. Novel alarmin-blocking and crystal-dissolving therapies are promising. Prescribing biologics, weaning steroids and treating subsequent exacerbations are rapidly evolving clinical challenges.